Variation in digital breast tomosynthesis image quality at differing heights above the detector. Issue 2 (27th December 2021) - Davidson, Rob; Al Khalifah, Khaled; Zhou, Abel
Abstract: Introduction: The aim of this preliminary work was to determine if image quality in digital breast tomosynthesis (DBT) changes when tomosynthesis image slices were obtained at differing heights above the detector and in differing breast thicknesses. Methods: A CIRS Model 020 BR3D breast imaging phantom was used to obtain the DBT images. The images were also acquired at different tube voltages, and each exposure was determined by the automatic exposure control system. Contrast‐to‐noise ratio (CNR) and figure‐of‐merit (FOM) values were obtained and compared. Results: At a phantom thickness of 5 cm or greater, there was a significant reduction ( P ≤ 0.05) of image CNR values obtained from the images near the top of the phantom to those obtained near the bottom of the phantom. When the phantom thickness was 4 cm, there was no significant difference in CNR values between DBT images acquired at any height in the phantom. FOM values generally showed no difference when images were obtained at differing heights above the detector. Conclusion: Image quality, as measured by the CNR, was reduced when tomosynthesis slice image heights were at the top of the phantom and when the thickness of the phantom was more than 4 cm. From this preliminary work, clinicians need to be aware that DBT images obtained near the top of the breast, when breast thickness is greater than 4 cm, may have reduced image quality. Further work is needed to fully assess any DBT image quality changes when images are obtained near the top of the breast. Abstract : Digital breast tomosynthesis (DBT) image quality has been assessed at different slice heights above the detector within a phantom. This initial work has shown that image quality differs when DBT slice image heights were at the top of the phantom compared to the bottom and when the phantom was greater than 4 cm thick. Clinicians need to be aware of this preliminary finding as a potential source of false negative findings when using DBT.